PENERAPAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN ARGUMENTASI TERTULIS SISWA KELAS X MIPA 2 SMA NEGERI 5 SURAKARTA PADA MATERI EKOSISTEM - Novian Budi Tama (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2015)
The objectives of this research was to improve students written argumentation on Ecosystem material in class X Science 2 SMA Negeri 5 Surakarta through the aplication of projcet based learning. This research was a class room action research conducted in three cycle. Every cycle consists of 4 stages, namely: planning, action, observing and reflecting. The subject of this research was the students in X Science 2 of SMA Negeri 5 Surakarta academic year 2014/2015 that are 30 students. The data of this research are obtained from the test, observationand documentation. Data validation of this research was triangulation method. This research was descriptive qualitative research which was analyzed through three component analysis: data reduction, data presentation, and taking the conclusion or verification. This research uses spiral model. The result of this research shows that the aplication of project based learning improved students written argumentation skill. Students written argumentation skill was 22,04% in the pre-cycle, 30,48 in theÂ  first cycle, 25,74% in the second cycle, and 32,01% in the third cycle. The reasearch conclution is the implemantation of project based learning can improve students written argumentation skill on Ecosystem material in class X Science 2 SMA Negeri 5 Surakarta